A Cross-Section Survey Assessment Study on the Prevalence of Knowledge and Awareness toward the Attitude on the Severity of Food Allergy among the Saudi Population of Jeddah Region - Iqubal, Dr. S. M. Shakeel (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Food Allergy (FA) is an adverse immune reaction triggered by a specific food antigen. It can be immunoglobulin (Ig) E-mediated or non-IgE-mediated, or mixed. FA is a common life-threatening condition that can affect families’ well-being. We conducted our study based on a study done in the Al-Taif city, Saudi Arabia. This study aimed to measure and raise awareness regarding the causes, severity, and symptoms of FA in Jeddah, Saudi Arabia. Materials and Methods: A cross-sectional study was conducted on 2060 participants. Data were collected through a self-reported modified questionnaire, randomized, online-based questionnaire, and direct interview with the campaign’s participants, which were performed from October 2019 to November 2019. The designed questionnaire encompassed demographic information such as age, gender, and educational level and ten comprehensive questions regarding FA. Results and Discussion: Most subjects had a FA (65.6%). The FA was mostly to eggs (46.3%), then seafood (30.4%), dairy foods (21.2%), and nuts (20.3%). Moreover, most allergy symptoms were moderate (52.6%), while severe was (13.1%). Most allergy symptoms were itching (57.7%) followed by dyspnea (36.2%) body swelling (26.5%). Regarding the awareness score range from 0 to 6, with 0 being the lowest score, and 6 being the highest score, the participants who had terrible scores were significantly higher than those with adequate scores. Subjects with food allergies had a more adequate awareness score than those without food allergies (47.7% vs. 13. 1%). Conclusion: A health education program about food allergies should be designed and conducted to educate our population about food allergies, treatment options, severity, and possible causes. It is also recommended to have a national day in Saudi Arabia to educate the population about food allergies, especially mothers and children.